Dynamic web page protection based on content integrity. (27th December 2006) - Lin, Da-Wei; Chen, Yi-Ming
The web is the most widely available service on the internet, but it is difficult to bullet-proof a web system. In this research, an integrity-based web page protection method is proposed to ensure that the service provided is as expected from the original business logic design. In our method, integrity violation means that an error has occurred. The proposed method is lightweight and the false alarm rate is extremely low. Management of signature updating is not needed. Finally, the experimental performance of the system is better than that of the traditional signature-based detection systems, and has little impact on system performance.